Molecular assessment of bacteriophage genome as a potential therapeutic agent in treating multi-drug resistant bacterial infection - Tabassum, Mehnaz (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.